Modeling of wear-resistance of electro-spark coatings without lubricant - Варюхно, В.В.; Довгаль, А.Г.; Бурдюженко, Л.В.; Лісовий, Є.М. (Proceedings of National Aviation University, 2004)
In the article experimental data on wear-resistance of electro-spark coatings an aluminum alloy Ал-25 by copper electrode is given. Planning of experiment and mathematical modeling wear-resistance and friction factor is made. An analysis of models is performed.